Crop water production functions for grain sorghum and winter wheat - Moberly, Joseph (Kansas State University, 2016)
Productivity of water-limited cropping systems can be reduced by untimely distribution of water as well as cold and heat stress. The research objective was to develop relationships among weather parameters, water use, and grain productivity to produce production functions to forecast grain yields of grain sorghum and winter wheat in water-limited cropping systems. Algorithms, defined by the Kansas Water Budget (KSWB) model, solve the soil water budget with a daily time step and were implemented using the Matlab computer language. The relationship of grain yield to crop water use, reported in several crop sequence studies conducted in Bushland, TX; Colby, KS and Tribune, KS were compared against KSWB model results using contemporary weather data. The predictive accuracy of the KSWB model was also evaluated in relation to experimental results. Field studies showed that winter wheat had stable grain yields over a wide range of crop water use, while sorghum had a wider range of yields over a smaller distribution of crop water use. The relationship of winter wheat yield to crop water use, simulated by KSWB, was comparable to relationships developed for four of five experimental results, except for one study conducted in Bushland that indicated less crop water productivity. In contrast, for grain sorghum, experimental yield response to an increment of water use was less than that calculated by KSWB for three of five cases; for one study at Colby and Tribune, simulated and experimental yield response to water use were similar. Simulated yield thresholds were consistent with observed yield thresholds for both wheat and sorghum in all but one case, that of wheat in the Bushland study previously mentioned. Factors in addition to crop water use, such as weeds, pests, or disease, may have contributed to these differences. The KSWB model provides a useful analytic framework for distinguishing water supply constraints to grain productivity.
Keywords: Kansas Water Budget; Matlab; Grain sorghum; Winter wheat; Dryland cropping systems; Crop water use